2018
DOI: 10.1111/ecc.12951
|View full text |Cite
|
Sign up to set email alerts
|

The nature and timing of distress among post-treatment haematological cancer survivors

Abstract: Many people with haematological cancers will not meet the diagnostic criteria for a psychological disorder, but will still suffer distress during treatment and beyond. The current study aimed to explore the nature and timing of psychosocial distress experienced by haematological cancer survivors. Twenty‐three post‐treatment haematological cancer survivors participated in a semi‐structured interview. Data were analysed using thematic analysis which involved identifying, analysing and reporting themes. Four them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Due to improvements in treatment modalities and decreasing mortality rates following HSCT the number of survivors is increasing (12)(13)(14). While many HSCT-survivors struggle with self-management and adherence to their prescribed care (15) little is known about survivors' perspective on how long-term effects of alloHSCT impact on their lives, and how healthcare providers could better help them manage their symptoms and care (16,17). For example, Laidsaar-Powell et al conducted a recent review on adult cancer survivors and found that compared to other common cancers with relatively high survival rates, such as breast or prostate cancer, there is considerably little evidence about the perceptions and experiences of survivors of hematological cancers, particularly with regard to the long-term effects of alloHSCT, such as cGvHD (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Due to improvements in treatment modalities and decreasing mortality rates following HSCT the number of survivors is increasing (12)(13)(14). While many HSCT-survivors struggle with self-management and adherence to their prescribed care (15) little is known about survivors' perspective on how long-term effects of alloHSCT impact on their lives, and how healthcare providers could better help them manage their symptoms and care (16,17). For example, Laidsaar-Powell et al conducted a recent review on adult cancer survivors and found that compared to other common cancers with relatively high survival rates, such as breast or prostate cancer, there is considerably little evidence about the perceptions and experiences of survivors of hematological cancers, particularly with regard to the long-term effects of alloHSCT, such as cGvHD (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The need to carry out this study took inspiration from the observation that in the literature, few studies have analyzed psychological distress in lymphoma survivors who were at least 5 years after the end of treatments, and frequently, data must be extrapolated from generic cancer and/or hematological survivor samples ( Linden et al, 2012 ; Korszun et al, 2014 ; ACTION Study Group, 2017 ; Oberoi et al, 2017 ; Bevilacqua et al, 2018 ; Kuba et al, 2019 ; Raphael et al, 2019 ; Götze et al, 2020 ; Joshy et al, 2020 ). It is also important to consider that studies often speak generically of psychological distress without distinguishing the components of anxiety and depression ( Korszun et al, 2014 ; Jones et al, 2015 ; Raphael et al, 2019 ; Troy et al, 2019 ; Joshy et al, 2020 ). In addition, the literature shows that lymphoma survivors often have specific characteristics (such as: <QoL, pain, depression, and anxiety) because the clinical processes and therapies they undergo produce strong adverse effects ( Vargas-Román et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that patients with lymphoma have a greater intensity of psychological distress in the treatment phase than lymphoma survivors ( Smith et al, 2009 ; Troy et al, 2019 ). However, it was also found that anxiety and depression are among the consequences experienced by cancer survivors and that their levels change with the passage of time ( Raphael et al, 2019 ; Troy et al, 2019 ). Therefore, it is important to assess psychological distress along the entire survival trajectory and offer timely responses of adequate psychological support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Квалитативно истраживање на узорку од 23 хемато-онколошка пацијента у периоду након лечења показало је да је дистрес након завршетка лечења углавном повезан са физичким проблемима и последицама болести и лечења. Слично као у нашем истраживању, у овом истраживању је добијено да је дистрес након завршетка лечења узрокован страхом од релапса болести (Raphael, Frey, & Gott, 2018). У нашем истраживању значајан број пацијената наводи бригу о новцу и рачунима, те проблеме на послу/школи, као проблеме који их од осталих наведених практичних проблема највише потресају, што указује на то да су приходи и активности током трајања онколошког лечења, а често и у периоду рехабилитације, након лечења, значајно редуковани, што отежава функционисање пацијената и представља додатни извор бриге.…”
Section: дискусијаunclassified